Application of Statistical Solvent Mixture Design in Optimizing the Solid-Liquid Extraction of Phenolic Compounds from Mango Seed Kernels - Cabajar, Alden A.; Siacor, Francis Dave C.; Lim, Kramer Joseph A.; Lobarbio, Camila Flor Y.; Taboada, Evelyn B. (Applied Science and Engineering Progress, 2021)
Mango seed kernel (MSK) is a waste material of the mango processing industry and is reported to significantly contain phenolic compounds with anti-oxidative properties. In this work, these compounds are isolated via solid-liquid extraction (SLE) in which solvent mixture design approach was used to evaluate the optimal quaternary solvent ratio in relation to the phenolics content of extracts from MSK. The quaternary solvent is composed of ethanol (E), methanol (M), acetone (A), and water (W). The extraction process was implemented at 40°C for 60 minutes with the ratio between solid and solvent at 1:25. Response surface methodology coupled with simplex lattice design was developed to evaluate the optimal solvent system and their interaction effects on the phenolic compounds content. The linear, two-way, and three-way interaction, except for methanol-acetonewater system, resulted in positive effects on the phenolic compounds content. The response model shows that a quaternary mixture with approximately 3:3:3:1 E:M:A:W ratio provided the highest phenolic content. A Scheffé cubic model sufficiently described the extraction process. The results of this study showed that the extraction of phenolic compounds in MSK via SLE using a mixture of solvents is possible. Higher extraction efficiencies can be achieved by optimizing the SLE process, and the optimum conditions can be applied to produce phenolic extracts with positive antioxidant activity.